PENDIDIKAN SEJARAH DAN PERMASALAHAN YANG DIHADAPI - Magdalia Alfian (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2011)
This paper elaborated the education of history and his problems in Indonesia. There are some problems in the education of history in Indonesia. Beside the educational curriculum has been always changed, as few as learned matter, and problem of historical learning in classroom in which the education of history was considered as a wearied subject matter. That one of effort to solve the last problem is historical trip, make a trip to historic sites. Key Words: the educaton of history, historical trip.